Die europäischen Arten der Gattung Lysiphlebus Foerster (Hymenoptera: Braconidae, Aphidiinae). Eine monographische Revision. - Mackauer, Manfred (Contributions to Entomology = Beiträge zur Entomologie, 1960)
The publication gives a monographic revision of the species of the genus Lysiphlebus Foerster (Hymenoptera: Braconidae, Aphidiinae). The biology has been considered detailed; especially it is given a revised list of hosts. There are discussed the relationships and the phylogenetic evolution as well of the genus as of the single species. The species united as "Lysiphlebus fabarum-testaceipes-group" are specially examined.There are new described three species. The genotype Aphidius dissolutus (Nees 1811) sensu Nees 1834 is treated as species dubia.Nomenclatural Actscardui Marshall, 1896 (Aphidius), syn. n. of Lysiphlebus Lysiphlebus ambiguus (Haliday, 1834)fabarum Marshall, 1896 (Lysiphlebus), syn. n. of Lysiphlebus Lysiphlebus ambiguus (Haliday, 1834)Platycyphus Mackauer, 1960 (Lysiphlebus), sgen. n.ambiguus (Haliday, 1834) (Lysiphlebus (Lysiphlebus)), comb. n. hitherto Aphidius (Aphidius) ambiguus Haliday, 1834fritzmuelleri Mackauer, 1960 (Lysiphlebus (Lysiphlebus)), spec. n.hirticornis Mackauer, 1960 (Lysiphlebus (Lysiphlebus)), spec. n.janinii (Quilis, 1930) (Lysiphlebus (Lysiphlebus)), syn. n. of Lysiphlebus (Lysiphlebus) ambiguus (Haliday, 1834)macrocornis Mackauer, 1960 (Lysiphlebus (Platycyphus)), spec. n.